PENGARUH BAURAN PEMASARAN TERHADAP MINAT BELI KONSUMEN (Studi Kasus Pada Penjualan Jasa Kamar Hotel Ratu Mayang Garden Pekanbaru) - Melva Elfrida Sinaga; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research was done in Hotel Ratu Mayang Garden Pekanbaru, the purpose of this research is to know the influence of promotion mixed towards customers interest buying (case study the room service sales of Hotel Ratu Mayang Garden Pekanbaru). The promotion mixed as independent variable (X) while customers interest buying (Y).The problem of this research is level of room service sales of Hotel Ratu Mayang Garden couldn’t reach the target, moreover seems decreasing every year. It has been seen from the realization percentage of room service sales of hotel level in last 4 years. This sample has taken about 100 respondent of population which is calculating using slovin formula. The data was getting from questionnaire and process next to test with statistic by SPSS program.The result shown that promotion mixed has positive effect about 63% and significant towards customers interest buying of the room service sales of Hotel Ratu Mayang Garden Pekanbaru.Key words: promotion mixed, customers interest buying